2011
DOI: 10.2220/biomedres.32.73
|View full text |Cite
|
Sign up to set email alerts
|

Restricted expression of somatostatin receptor 3 to primary cilia in the pancreatic islets and adenohypophysis of mice

Abstract: The primary cilium is now considered to function as a fundamental, not rudimentary, structure for mechanical and chemical sensing by individual cells. Primary cilia in neurons express type III adenylyl cyclase (ACIII) and GPCRs for somatostatin (somatostatin receptor 3, SSTR3), serotonin, and melanin-concentrating hormone. The present immunohistochemical and electron microscopic study revealed an abundant occurrence of SSTR3-expressing solitary cilia in insulin-and growth hormone-secreting cells of the mouse. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 37 publications
(43 reference statements)
6
31
0
Order By: Relevance
“…The D2R antibody used selectively stained the striatum in the mouse brain (33) but never stained any structures in the adrenal gland or pancreatic islets. SSTR3 and AC3 antibodies used specifically labeled the primary cilia on neurons in several regions of the mouse brain, in agreement with previous studies (24). The specificity of immunoreactions with the anti-D2R antibody was confirmed by disappearance of the immunoreactivity when the antibody was preincubated with a peptide antigen (Frontier Institute Co.Ltd).…”
Section: Animalssupporting
confidence: 88%
See 1 more Smart Citation
“…The D2R antibody used selectively stained the striatum in the mouse brain (33) but never stained any structures in the adrenal gland or pancreatic islets. SSTR3 and AC3 antibodies used specifically labeled the primary cilia on neurons in several regions of the mouse brain, in agreement with previous studies (24). The specificity of immunoreactions with the anti-D2R antibody was confirmed by disappearance of the immunoreactivity when the antibody was preincubated with a peptide antigen (Frontier Institute Co.Ltd).…”
Section: Animalssupporting
confidence: 88%
“…Electron microscopic studies of these endocrine cells have demonstrated the existence of single cilia which display a structural organization unlike that of the motile cilia (5,45,49). Our recent immunohistochemical study revealed an abundance of SSTR3-expressing solitary cilia in growth hormone (GH)-secreting cells and insulin-secreting β-cells of the mouse (24). Further application of immunostaining for various receptors in the nervous and endocrine tissues holds promise for establishing the primary cilia as universal sensory devices.…”
mentioning
confidence: 95%
“…To investigate ciliary changes in the hypothalamus in mouse models of obesity, cilia were immunostained using an antibody against adenylate cyclase 3 (AC3) (8). Immunohistochemistry for somatostatin receptor 3 (SSTR3), another marker used to identify cilia in neurons (9), labeled only about 30%-50% of AC3-immunoreactive cilia in the hypothalamus (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI69395DS1). Nevertheless, the complete overlap of AC3 and SSTR3 staining along the entire length of the cilia confirmed that AC3 is a useful marker for analyzing cilia length.…”
Section: Resultsmentioning
confidence: 99%
“…Lean mass growth that is driven by growth hormone is regulated by hypothalamic hormones, including somatostatin (38). Somatostatin receptor 3 (SSR3) is localized to the primary cilium (39), and its function may be affected by RPGRIP1L action. It is plausible that RPGRIP1L action in hypothalamic cilia may also regulate body growth through effects on SSR3.…”
Section: Discussionmentioning
confidence: 99%